Integrating Strategy of Network Pharmacology, Molecular Dynamics Simulation, and Experimental Verification to Investigate the Potential Mechanism of Gastrodia elata Against Alcoholic Liver Injury - Peiyuan Sun; Ruohan Zhang; Xuanyou Li; Dengwang Yang; Shunfeng Ji; Lei Peng; Jun Sheng; Jing Wang (Foods)
As one of the medicinal and edible resources, Gastrodia elata (GE) is considered to hold potential in alleviating alcoholic liver injury, yet its mechanism needs further elucidation. To explore the molecular mechanisms of GE against alcoholic liver injury, network pharmacology, molecular docking, molecular dynamics simulations, and cell experiments were employed. Thirty-two active components of GE may exert efficacy against alcohol-induced liver injury via regulating 207 targets. Among them, the main functional components might be 4-hydroxybenzyl methyl ether, 4-ethoxytolyl-4′-hydroxybenzyl ether, pseudolaric acid B, palmitic acid, and myricetin. Analyses of Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment showed that a total of 322 GO items and 154 KEGG pathways are related to the effects of GE against alcoholic liver injury. The results of molecular docking show that the main active components of GE might interact with the key target proteins of GAPDH, PPARG, EGFR, STAT3, and AKT1. Molecular dynamics simulation further determined that pseudolaric acid B, as the core component, stably binds to these key target proteins. Cell experiments demonstrate that pseudolaric acid B exhibits a protective effect on ethanol-induced HepG2 cell injury by down-regulating the protein expression levels of GAPDH, STAT3, PPARG, and EGFR. Furthermore, the agent also suppresses IL-6 and inhibits the abnormal absorption of total cholesterol in HepG2 cells. Our findings suggest the efficacy and mechanism of GE in combating alcoholic liver injury and lay the groundwork for the precise development and utilization of GE.